(untitled) (Archives of Clinical and Medical Case Reports, 2019)
Femoro-acetabular impingement is a recognized mechanism for the development of early degenerative changes of the hip joint. The symptoms and progression of CAM femoro-acetabular impingement may be attenuated by conservative treatment, but surgical intervention is often necessary. Nowadays there is a trend towards open or arthroscopic operative correction with the aim to remove the cause of impingement at the acetabular rim and at the femoral head neck junction- but complications do occur. Recently conservative measures in FAI have been reported, reserving surgery to symptomatic patients. We present the case of a 40 year follow- up of conservatively treated symptomatic CAM Impingement of both hips.